2020
DOI: 10.1371/journal.pone.0237349
|View full text |Cite
|
Sign up to set email alerts
|

Non-response in a national health survey in Germany: An intersectionality-informed multilevel analysis of individual heterogeneity and discriminatory accuracy

Abstract: Background Dimensions of social location such as socioeconomic position or sex/gender are often associated with low response rates in epidemiological studies. We applied an intersectionalityinformed approach to analyze non-response among population strata defined by combinations of multiple dimensions of social location and subjective health in a health survey in Germany. Methods We used data from the cross-sectional sample of the German Health Interview and Examination Survey for Adults (DEGS1) conducted betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…In Denmark, ethnic minorities, place of residence, language, and presence of illness affected the decline in participation rates [ 33 , 34 ]. In some countries, an association between participation rates and socioeconomic status or gender has been reported [ 13 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark, ethnic minorities, place of residence, language, and presence of illness affected the decline in participation rates [ 33 , 34 ]. In some countries, an association between participation rates and socioeconomic status or gender has been reported [ 13 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…People’s lifestyles have been diversifying, and these situations differ by region [ 12 ]. In other countries, it has been reported that the population structure affects the response rate of surveys [ 13 , 14 ] and may lead to regional differences [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We applied multilevel analysis of individual heterogeneity and discriminatory accuracy (MAIHDA) [23,[35][36][37][38] to explore the effects of SDoH on three health outcomes via intersectionality. Unlike common measures of average association, MAIHDA allows for a better understanding of the heterogeneity of individual effects and inter-individual heterogeneity around group averages [23].…”
Section: Methodsmentioning
confidence: 99%
“…MAIHDA provides a feasible way of measuring multiple intersections and analysing groups of small size from an intersectionality perspective. MAIDHA also provides a parsimonious way of analysing high dimensional interactions which is not possible with single level models [23,38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation